Public relations ethics: how to practice PR without losing your soul - Martin, Dick (Unites States of America : Business Expert Press, 2016)
This book offers a practical guide to ethical decision-making tailored specifically to the needs of those who practice and study public relations. The book traces the development of ethical theory from ancient Greece through the works of Socrates, Plato, and Aristotle to modern day public relations executives.
1. Introduction -- 2. Is public relations inherently unethical? -- 3. Virtue and character -- 4. Public relations of character -- 5. Veracity, visibility, and validity -- 6. Respect for reason -- 7. The public interest -- 8. Corporate responsibility -- 9. Duties and rights -- 10. Care and justice -- 11. Ethical decision making -- 12. Frameworks for ethical reasoning -- 13. Constructing a personal framework for ethical reasoning -- 14. Conclusion .
Includes bibliographical references and index.
Keywords: CORPORATE COMMUNICATION